Legislative Research for Identification of Discriminatory Provisions in Existing Laws of Bangladesh - School of Law, BRAC University; Legislative Research and Reform for Promoting and Enforcing Non-discriminatory Laws and Policies project, Legislative and Parliamentary Affairs Division, Ministry of Law, Justice and Parliamentary Affairs (Legislative and Parliamentary Affairs Division, Ministry of Law, Justice and Parliamentary Affairs and School of Law, BRAC University, 2020)
The agreement made between School of Law, BRAC University and Legislative and Parliamentary Affairs Division, Ministry of Law, Justice and Parliamentary Affairs for the project 'Legislative Research for Identification of Discriminatory Provisions in Existing Laws of Bangladesh'.